Matematyka kultury, czyli jak policzyć charakter kulturowy miasta? - Klekotko, Marta (Człowiek i Społeczeństwo, 2019)
The purpose of the article is to critically discuss the methodology for measuring „urban scenes” which has been proposed by contemporary Chicago School. The author presents the assumptions and conceptual-analytical framework of scene theory, and then discusses the consecutive steps of the research strategy developed by this theory. The author refers to her research experience in using the scene approach and points to challenges and problems in the application of the scene theory, as well as proposes some strategies of overcoming them. Marta Klekotko, Marta Klekotko, Matematyka kultury, czyli jak policzyć charakter kulturowy miasta? [Marta Klekotko, Matematyka kultury, czyli jak policzyć charakter kulturowy miasta? [Mathematics of culture: how to measure cultural character of a city?] edited by M. Nowak, „Człowiek i Społeczeństwo” vol. XLVIII: Kuchnia badań miejskich. Studia na temat praktyki empirycznej badaczy miasta [A backstage of urban research. Studies on the empirical practices of city research scientists], Poznań 2019, pp. 13–34, Adam Mickiewicz University. ISSN 0239-3271. Marta Klekotko, Uniwersytet Jagielloński, Instytut Socjologii UJ, ul. Grodzka 52, 31-044 Kraków, e-mail: marta.klekotko@uj.edu.pl